The function f(x) - g(x) is an illustration of a composite function
Leanne's end result of f(x) - g(x) = -1/2x + 9 is correct
<h3>How to estimate the student's answer?</h3>
The functions are given as:
f(x) = 1/2x + 6
g(x) = x - 3
The function f(x) - g(x) is calculated using:
f(x) - g(x) = 1/2x + 6 - x + 3
Collect like terms
f(x) - g(x) = 1/2x - x + 6 + 3
Evaluate the like terms
f(x) - g(x) = -1/2x + 9
By comparing the above solution to the students' response, we can see that:
Leanne's end result of f(x) - g(x) = -1/2x + 9 is correct
Read more about composite functions at:
brainly.com/question/13502804